PEMANFAATAN CERITA FABEL “KURA-KURA YANG PINTAR” KARYA LENI ARYANI SEBAGAI MEDIA PENGEMBANGAN BAHASA PADA USIA DINI 4-6 TAHUN - Mila Rosa Amelia; Khaerunnisa (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Language skills consist of four components, namely speaking, writing, listening and reading. The most important thing for children is talking, because it provides enormous benefits, one of which is so that children can interact with their peers and other people around them and can add new knowledge. Storytelling is a communication medium that is favored by children, training their ability to discuss attention for a certain period of time. Children are able to express themselves through a process that makes them happy and creates a sense of satisfaction that makes them more confident. Fables are fairy tales with animals as characters. The benefits of fable stories are to train children's language skills. When telling or listening to stories, children learn to speak in a fun style and increase their vocabulary and language. Keywords: language, early childhood, story, fable